Learning from calorie posting/traffic light systems introduction in a University hospital canteen. (13th November 2019) - Fitzpatrick, P; Flood, C; Cuniffe, E; Doherty, K; Lyons, A; Stynes, S; Pilkington, A; Barnes, L; Peare, T; Kelleher, C C
Abstract: : Calorie posting is now policy in hospitals in Ireland and restaurants will be required to display calorie counts on menus by end of 2019. The Health Promotion, Dietetics and Catering teams worked together to introduce calorie posting and a traffic light system (TLS) for all foodstuffs available in the staff canteen of a large University teaching hospital in Dublin, Ireland. A calorie posting launch took place in September 2018. The aim of this study was to determine staff perception of calorie posting and TLS. One month after the launch, 343 staff members were surveyed using a short pre-designed Sphynx-software questionnaire at 3 time points daily over one week, at breakfast, lunch and evening mealtimes. SPSS was used for analysis. Of the 353 respondents (65.3% female; 18-44 years 65.3%, 45+ 32.1%, unknown 2.6%), more staff found calorie posting helpful compared to TLS (66.5% vs 43.7%; p = 0.001). Staff stated they made themselves aware of calorie count always/mostly (46%) and sometimes (26.2%). More females than men found both calorie posting (72.3% vs 53.3%; p = 0.001) and TLS (49.1% vs 31.8%; p = 0.001) helpful. More respondents identified calorie posting than TLS as influencing food choice at least sometimes (60.3% vs 36%; p = 0.0001). Females were more likely to make a food choice change based on TLS (39.7 vs 20.6%; p = 0.01). Age and frequency of canteen use were not associated with either. The results suggest calorie posting is used rather than TLS by all hospital staff and female hospital staff are likelier to use both. Learning from this study, the positioning of TLS in relation to individual foodstuffs has been reviewed, further promotion of TLS/calorie posting has taken place in the hospital and a regular audit has been established. Notwithstanding the challenges, important moves towards healthier choices were seen. Key messages: Introduction of traffic light system and calorie posting needs evaluation. Females appear more likely to avail of traffic light systems and calorie posting in relation to food choices.